College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 5, Systems of Equations and Inequalities - Section 5.2 - Systems of Linear Equations in Several Variables - 5.2 Exercises - Page 455: 9



Work Step by Step

Given: $x+2y+z=7; -y+3z=9; 2z=6$ Here $2z=6 \implies z=3$ Plug $z=3$ in the second equation. we get $-y+3(3)=9 \implies y=0$ Now, Plug $y=0,z=3$ in the first equation. we have $x+2(0)+3=7$ or, $x=7-3 \implies x=4$ Hence, the solution is:$(x,y,z)=(4,0,3)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.